Effect of adding oat bran to instant oatmeal on glycaemic response in humans – a study to establish the minimum effective dose of oat β-glucan. Issue 3 (26th February 2018) - Wolever, Thomas M. S.; Jenkins, Alexandra L.; Prudence, Kevin; Johnson, Jodee; Duss, Ruedi; Chu, YiFang; Steinert, Robert E.
Abstract : The slope of the present dose–response curve for low-dose oat β-glucan (g/g available-carbohydrate) is equivalent to that for high doses. Abstract : Reducing the glycaemic response to carbohydrate-containing foods may have desirable physiological effects for many people. Here, we aimed to determine the minimum amount of oat β-glucan from oat-bran which, when added to instant-oatmeal, would reduce the glycaemic response by 20% compared to a β-glucan-free cereal. Therefore, the glycaemic responses elicited by one serving (27 g) instant-oatmeal plus 247 g 2% milk (IO, 28 g available-carbohydrate, 1.2 g β-glucan) or IO plus 0.2, 0.4, 0.8 or 1.6 g oat β-glucan (OBG) from oat-bran, or an available-carbohydrate matched portion of cream of rice (CR) plus milk were measured over 2 h in n = 40 subjects using a randomized, cross-over design. The primary endpoint was incremental area under the curve (iAUC). The secondary endpoint was glucose peak-rise. The results showed that grams OBG consumed were significantly correlated with mean iAUC ( p = 0.009) and with mean glucose peak-rise ( p = 0.002). Each gram of OBG reduced iAUC by 7% and peak-rise by 15%. Thus, to achieve a ≥20% reduction in iAUC relative to CR, 1.6 g OBG had to be added to IO (74 ± 7 vs. 93 ± 6 mmol min L −1, p < 0.05), but, to achieve a 20% reduction in peak-rise, only 0.4 g OBG was required (2.00 ± 0.1 vs. 2.40 ± 0.1 mmol, p < 0.05). We conclude that adding OBG to IO flattened postprandial glycaemic responses in a dose-dependent fashion; 1.6 g OBG was required to reduce iAUC by ≥20% versus CR, but a 20% reduction in peak-rise required only 0.4 g. The greater effect of OGB on peak-rise than iAUC presumably reflects the way viscous dietary fibres modulate glucose absorption kinetics.